Menyikapi Budaya Kekerasan - Zaenul Mahmudi (UIN Maulana Malik Ibrahim Malang, 2002)
Violence that occurred during the reign of Abdurrahman Wahid, whether nuanced, religion, race and intergroup (SARA) or nuanced disintegration of the nation can not be seen from the side lahiriyah, but the violence needs to be studied in depth from various aspects which surrounds it, as Abdurrahman Wahid's rise as president is a national compromise reflected in his cabinet structure that seeks to accommodate the aspirations of all political contestants who participate in the elections, so the cabinet is called the